1991
DOI: 10.1021/bi00242a014
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary structure of conotoxin GIIIA in aqueous solution

Abstract: The three-dimensional structure of conotoxin GIIIA, an important constituent of the venom from the marine hunting snail Conus geographus L., was determined in aqueous solution by two-dimensional proton nuclear magnetic resonance and simulated annealing based methods. On the basis of 162 assigned nuclear Overhauser effect (NOE) connectivities obtained at the medium field strength frequency of 400 MHz, 74 final distance constraints of sequential and tertiary ones were derived and used together with 18 torsion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
104
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 37 publications
5
104
1
Order By: Relevance
“…The potency reductions produced by Ala substitutions were primarily due to the direct interaction of the essential residues Lys 27 and Arg 29 with sodium channels rather than to a conformational change. After comparison of these structures and activities with correlated toxins, we hypothesized that residues Lys 27 clustered on one face of HNTX-IV were responsible for ligand binding.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The potency reductions produced by Ala substitutions were primarily due to the direct interaction of the essential residues Lys 27 and Arg 29 with sodium channels rather than to a conformational change. After comparison of these structures and activities with correlated toxins, we hypothesized that residues Lys 27 clustered on one face of HNTX-IV were responsible for ligand binding.…”
mentioning
confidence: 96%
“…Based on the structural comparison and sequence assignment with other related toxins, we hypothesized that the positively charged residues Arg 26 , Lys 27 , and Arg 29 in loop IV and vicinal polar residue Ser 12 clustered on one face of HNTX-IV may be the potential interaction site. Mutants S12A, R26A, K27A, and R29A were synthesized by solid-phase Fmoc chemistry followed by oxidative refolding of purified peptides under the optimal conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). Some other proteins present the same connectivity, e.g., Escherichia coli enterotoxin (Garitpy et al, 1986) and conotoxin GIIIA (Lancelin et al, 1991); however, no loop penetration (Klapper & Klapper, 1980) can be observed in these structures.…”
mentioning
confidence: 99%
“…5. The NMR structures of the muscle selective GIIIA (Lancelin et al 1991) may not reflect the structure that binds the VGSC based on comparisons with NMR structure of TIIIA ).…”
Section: M-conotoxinsmentioning
confidence: 99%